1992
DOI: 10.1083/jcb.119.6.1669
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor withdrawal-induced cell death in neuronal PC12 cells resembles that in sympathetic neurons.

Abstract: Abstract. Previous studies have shown that in neuronal cells the developmental phenomenon of programmed cell death is an active process, requiring synthesis of both RNA and protein. This presumably reflects a requirement for novel gene products to effect cell death. It is shown here that the death of nerve growth factor-deprived neuronal PC12 cells occurs at the same rate as that of rat sympathetic neurons and, like rat sympathetic neurons, involves new transcription and translation. In nerve growth factor--de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
124
1
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(144 citation statements)
references
References 43 publications
(77 reference statements)
18
124
1
1
Order By: Relevance
“…A characteristic of PC12 cells is the reversibility of their di erentiation when treated with NGF in serum-containing medium. However, when induced to di erentiate by NGF in serum-free medium, PC12 cells exhibit dependence on NGF for their survival and undergo programmed cell death in its absence via mechanisms highly similar to terminally di erentiated sympathetic neurons (Mesner et al, 1992). As shown here, ectopic expression of E2F2 essentially converts di erentiated PC12 cells from a reversibly to a`terminally' di erentiated, NGFdependent state.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A characteristic of PC12 cells is the reversibility of their di erentiation when treated with NGF in serum-containing medium. However, when induced to di erentiate by NGF in serum-free medium, PC12 cells exhibit dependence on NGF for their survival and undergo programmed cell death in its absence via mechanisms highly similar to terminally di erentiated sympathetic neurons (Mesner et al, 1992). As shown here, ectopic expression of E2F2 essentially converts di erentiated PC12 cells from a reversibly to a`terminally' di erentiated, NGFdependent state.…”
Section: Discussionmentioning
confidence: 73%
“…We have examined this question using the pheochromocytoma cell line, PC12, which exits the cell cycle and di erentiates into sympatheticlike neurons following treatment with NGF. These cells have proven highly useful in examining many important aspects of neuronal di erentiation, including cell cycle mechanisms that regulate growth arrest and its interactions with the neuronal di erentiation program (Buchkovich and Zi , 1994;Mesner et al, 1992;Yan and Zi , 1995). In particular, PC12 cells exhibit reversible arrest and di erentiation upon treatment with NGF in serum-containing medium (Greene and Tischler, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…A typical feature of neuronal apoptosis is a requirement for new mRNA and protein synthesis (Johnson and Deckwerth, 1993). Mesner et al (1992) showed that actinomycin D and cycloheximide inhibit apoptosis in neuronal PC12 cells. We also Âźnd that gene activation and protein synthesis soon after addition of ceramide is required for apoptosis of SKN-SH cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat pheochromocytoma PC12 line, a commonly used model for neuronal differentiation and cell death, apoptosis may be triggered by either trophic factor/nerve growth factor (NGF) withdrawal (Greene, 1978;Batistatou and Greene, 1991;Rukenstein et al, 1991;Mesner et al, 1992;Pittman et al, 1993;Lindenboim et al, 1995) or oxidative stress induced by downregulation of Cu 2Ï© /Zn 2Ï© superoxide dismutase (SOD1) (Troy and Shelanski, 1994;Troy et al, 1996a-c). The initiating mechanisms of death seem to be distinct in each instance.…”
mentioning
confidence: 99%